Lymphopenia-Induced Proliferation in Aire-Deficient Mice Helps to Explain Their Autoimmunity and Differences from Human Patients - Kisand, Kai; Peterson, Pärt; Laan, Martti (Frontiers in Immunology, 2014)
Studies on autoimmune polyendocrinopathy candidiasis ectodermal dystrophy (APECED) and its mouse model – both caused by mutant AIRE – have greatly advanced the under-standing of thymic processes that generate a self-tolerant T-cell repertoire. Much is now known about the molecular mechanisms by which AIRE induces tissue-specific antigen expression in thymic epithelium, and how this leads to negative selection of autoreactive thymocytes. However, we still do not understand the processes that lead to the activation of any infrequent naïve auto-reactive T-cells exported by AIRE-deficient thymi. Also, the striking phenotypic differences between APECED and its mouse models have puzzled researchers for years. The aim of this review is to suggest explanations for some of these unanswered questions, based on a fresh view of published experiments. We bring evidence that autoreactive T-cells can be activated by prolonged neonatal lymphopenia that naturally develops in young Aire-deficient mice due to delayed export of mature thymocytes. Lymphopenia induced proliferation (LIP) fills the empty space favoring autoreactive T cells. This leads to lymphocyte infiltration in similar tissues as seen in day 3 thymectomised animals. LIP turns uncontrolled in Aire–/– crosses with other model mice with defects in genes responsible for anergy induction and Treg responsiveness, or defects in TCR signaling in combination with impaired function of homeostatic cytokines. In APECED patients LIP is probably not among the factors that participate in naïve autoreactive T cell activation as humans are born with more mature immune system in comparison to mice. We suggest that human AIRE-deficiency presents with different phenotype due to additional precipitating factors on top of deficient negative selection of tissue-specific thymocytes.